Authoritarian order versus democratic disorder (a review essay) - Chopra, Pran (2000)
P.N. Dhar's book gives a fascinating and authentic account of some of the major events and personalities which shaped India during the 1970s. The author was a close observer of that period, as well as an influence in shaping what he saw, and he now stands back, with the trained mind of a noted academic, to assess and analyse various themes - `Indira Gandhi', `the Emergency', and `Indian democracy'. The result is a major work of contemporary history. It demands the reader's closest attention, irrespective of whether he agrees or disagrees with the author, because the book is not only a chronicle but also the product of the author's own beliefs and values. Particularly important in this respect are P.N. Dhar's views on whether the Emergency was more the end result of Mrs Gandhi's own predilections or of such a breakdown of democracy that it had to be suspended to save it. - Reproduced
Keywords: Politics and government